Effectiveness of Educational Interventions in Improving Prescribing and Dispensing of Antibiotics in Pharmacy: A Systematic Review - Kandagor, Amos; Tenambergen, Wanja Mwaura; Mapesa, Job (International Journal of Professional Practice, 2023)
Inappropriate use of antibiotic has been a global problem, mostly affecting the developing countries. This is particularly so because developing countries are usually faced with shortage of objective information on antibiotic use. The purpose of this study was to assess the effectiveness of educational intervention measures used either alone or in combination, to optimize prescribing and dispensing of antibiotics. Guided by PRISMA guidelines, the study systematically reviewed literature obtained from PubMed, Cochrane Database and Google scholar, between January 1990 and December 2020. 4,524 articles and 20 studies were identified for analysis. The research included randomized control trial before and after the studies. The quality of the study was assessed on the basis of weight of evidence. All the studies reported positive results, where n (18) focused on improvement in use of antibiotics, and n (2) on knowledge of dispensers without measuring antibiotic use. Educational materials alone had little influence, 6% indicated reduction in antibiotic prescription, audit and feedback, 20%, cited local consensus; 42% trainings, while 54% suggested reduction of unnecessary prescribing of antibiotic. Multi-faceted interventions had n (14) studies, with average of 41% improvement in appropriate prescribing of antibiotic. The study concludes that effectiveness of educational interventions depends on the prescribing and dispensing behaviors, as well as barriers to change. Different interventions work well in some settings, while no single intervention sustained behavioral change. This study recommends multifaceted interventions, such as audit, feedback, academic detailing and practice guidelines directed by a pharmacist opinion leader.